2021
DOI: 10.3389/fmicb.2021.685670
|View full text |Cite
|
Sign up to set email alerts
|

Novel Identification of Bacterial Epigenetic Regulations Would Benefit From a Better Exploitation of Methylomic Data

Abstract: DNA methylation can be part of epigenetic mechanisms, leading to cellular subpopulations with heterogeneous phenotypes. While prokaryotic phenotypic heterogeneity is of critical importance for a successful infection by several major pathogens, the exact mechanisms involved in this phenomenon remain unknown in many cases. Powerful sequencing tools have been developed to allow the detection of the DNA methylated bases at the genome level, and they have recently been extensively applied on numerous bacterial spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 91 publications
1
13
0
Order By: Relevance
“…We investigated the location of unmethylated GATC motifs in X. nematophila F1, since such unmethylated sites could represent novel regulatory sites in the genome, where a competition between Dam and a DNA binding protein may occur [ 5 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We investigated the location of unmethylated GATC motifs in X. nematophila F1, since such unmethylated sites could represent novel regulatory sites in the genome, where a competition between Dam and a DNA binding protein may occur [ 5 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Such overexpression also caused an increase in the rate of GATC methylated sites recognized by Dam [ 30 ]. Because these sites were frequently located in promoter regions, the hypothesis of epigenetic regulations linked to competitions between the Dam MTase and DNA-binding proteins at these particular GATC sites was raised [ 30 , 31 ]. In a study on more than 200 bacterial species, methylation marks were reported in one strain of Xenorhabdus : they were mapping in three motifs, including GATC methylated by Dam [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of third-generation sequencing machines allowed the detection of the N6-methyladenosine (m6A) and of the other modified bases of the DNA, along with the simultaneous detection of the nucleotide sequence. Two platforms are available for the detection of modified bases on a genomic scale (Payelleville and Brillard, 2021 ): Single Molecule, Real-Time (SMRT) sequencing (Eid et al, 2009 ) and the Oxford Nanopore technology (ONT). These approaches don't involve a replication step during the library preparation, reducing the time required before sequencing, and allowing the preservation of all the modifications on the genome.…”
Section: Methods Used To Investigate Epigenetics In Bacteriamentioning
confidence: 99%
“…The development of TGS capable of reading single molecules has allowed a comprehensive study of frequency and distribution of epigenetic modifications. This way, it has been possible to discover that they may be related to different functions, including regulation of gene expression, maintenance of genome stability, cell cycle, sporulation, cell shape, biofilm formation, motility, siderophore generation, membrane vesicle production, defense (discriminating self from non-self DNA, like the bacteriophages that can be cut by restrictases), lysogenicity, virulence (including pathogen-host interactions and host colonization) and response to the environment [132,[135][136][137][138][139]. These studies are important to identify beneficial, harmless, opportunistic and pathogenic-virulent phenotypes related to health and disease [140].…”
Section: Epigenomicsmentioning
confidence: 99%
“…New sequencing methodologies allow to study epigenomics with an unprecedented resolutive power, including reduced-representation bisulfite sequencing (RRBS) and whole-genome bisulfite sequencing (WGBS), analyzing full genomes [154]. This has significant implications in many areas, such as ecology [155], environmental pollution including radiation [156,157], with relevant implications for cancer radioresistance [158] and health [135,138], as well neuropsychiatric disorders [159]. Besides, it has been found that mechanotransduction is involved in mechanical regulation of transcription and the epigenome, having a key role in cancer progression [160].…”
Section: Epigenomicsmentioning
confidence: 99%